The Role of Environmental Factors in Modulating Immune Responses in Early Life - MacGillivray, Duncan M.; Kollmann, Tobias R. (Frontiers in Immunology, 2014)
The concept of immunological memory stipulates that past exposures shape present immune function. These exposures include not only specific antigens impacting adaptive immune memory, but also conserved pathogen or danger associated molecular patterns that mold innate immune responses for prolonged periods of time. It should thus not come as a surprise that there is a vast range of external or environmental factors that impact immunity. The importance of environmental factors modulating immunity is most readily recognized in early life, a period of rapidly changing environments. We here summarize available data on the role of environment shaping immune development and from it derive an overarching hypothesis relating the underlying molecular mechanisms and evolutionary principles involved.